Como a mídia, no Brasil, apresenta o mercado de trabalho para pessoas com 60+? - Araujo, Denise Aparecida Pereira de (2014)
This research, qualitative and substantial, has had as main focus to identify, on national media, the job market speeches to 60+ people, basing on digital and printed press clippings, in order to verify market s compromise with the paradigm proposed by World Health Organization (WHO) which guides the current Active Aging Policy which in turn proposes continuous participation on socio-economic, cultural, spiritual and civic matters. 51 articles, conveyed between February and December of 2013, were selected and organized by its content, considering date, vehicle, region, cover story, titles, subtitles and focus; and initially classified in four categories: longevity, experience, retirement and entrepreneurship. Later, categories longevity and experience clustered in one, due their reference to similar themes. The articles from O Estado de S. Paulo, Valor Econômico e Revista Exame are intended to a high schooling and purchasing power public, while the other resorted vehicles (newscast, various information programs) direct to general public, some of whom, with low schooling levels. These articles provide maintenance or return to job market tips and inform how important it is to qualificate and update yourself. It was observed that media in this country is not following it s row on the Active Aging Policy agenda, because it does not inform population about their rights and duties, neither requires from society and the market, attitudes that make worth the definition of active , rescuing its dimension of optimizing opportunities